2007
DOI: 10.1021/bi700857u
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Ribonucleases:  The Dichotomy of Coulombic Forces

Abstract: Cells tightly regulate their contents. Still, nonspecific Coulombic interactions between cationic molecules and anionic membrane components can lead to adventitious endocytosis. Here, we characterize this process in a natural system. To do so, we create variants of human pancreatic ribonuclease (RNase 1) that differ in net molecular charge. By conjugating a small-molecule latent fluorophore to these variants and using flow cytometry, we are able to determine the kinetic mechanism for RNase 1 internalization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 55 publications
2
73
0
Order By: Relevance
“…Since cytotoxic RNases attack intracellular RNA, these RNases must be internalized. 41) Johnson et al 56) have suggested that a family of cationic onconases, the RNase A family from Rana pipiens, which exhibit strong anti-tumor activity, bind to the plasma membrane electrostatically, and that enzyme binding is therefore critical to their anti-cancer properties. We compared RNase Po1 to Onconase in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Since cytotoxic RNases attack intracellular RNA, these RNases must be internalized. 41) Johnson et al 56) have suggested that a family of cationic onconases, the RNase A family from Rana pipiens, which exhibit strong anti-tumor activity, bind to the plasma membrane electrostatically, and that enzyme binding is therefore critical to their anti-cancer properties. We compared RNase Po1 to Onconase in detail.…”
Section: Discussionmentioning
confidence: 99%
“…8) Johnson et al 19) have suggested that cationic onconases bind to the plasma membrane electrostatically, and that consequently enzyme binding is critical to the anti-cancer properties of onconases. Llinskaya et al 20) have reported that -sarcin is also cationic and hence is internalized by the same mechanism as onconases.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al proved this notion by creating a series of mutant human pancreatic RNases with different charge and analyzing the kinetics of their internalization. (31) The internalization increases with RNase concentration and reaches steady-state level, which varies linearly with molecular charge. However, the rate constant for internalization is independent of the charge.…”
Section: Penetration Of Rnases Inside the Cells And Its Role In Cytotmentioning
confidence: 99%